Spectroscopy of small molecules and clusters - Ayles, Victoria Louise (2008)
The 3s, 3d and 4s Rydberg states of nitric oxide (NO), bound to a rare gas (Rg) atom in a van der Waals complex (NO-Rg), are probed using resonance-enhanced multiphoton ionisation, in order to investigate the effect of electronic excitation on these complexes. The spectroscopy is interpreted in terms of interactions between the Rydberg electron, the nitric oxide (NO+) core and the Rg atoms. Larger NO-Rgx clusters are investigated offering the prospect of bridging the spectroscopic gap between van der Waals dimers and the bulk. The spectroscopy is determined by an NO+-Rg2 moiety and formation of the Rydberg state provokes a dynamic response from the Rgx cluster, similar to that observed in matrix studies.